2015
DOI: 10.1111/cas.12602
|View full text |Cite
|
Sign up to set email alerts
|

Boronophenylalanine, a boron delivery agent for boron neutron capture therapy, is transported by ATB0,+, LAT1 and LAT2

Abstract: The efficacy of boron neutron capture therapy relies on the selective delivery of boron carriers to malignant cells. p-Boronophenylalanine (BPA), a boron delivery agent, has been proposed to be localized to cells through transporter-mediated mechanisms. In this study, we screened aromatic amino acid transporters to identify BPA transporters. Human aromatic amino acid transporters were functionally expressed in Xenopus oocytes and examined for BPA uptake and kinetic parameters. The roles of the transporters in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
91
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(95 citation statements)
references
References 39 publications
(104 reference statements)
3
91
1
Order By: Relevance
“…Because LAT1 is a potential therapeutic target as well as a diagnosis biomarker of cancer, the inhibitors of LAT1 have been developed to suppress tumor growth . LAT1 can also be used for tumor‐targeted delivery of anti‐tumor agents such as melphalan and para‐boronophenylalanine in boron neutron capture therapy . Therefore, the LAT1‐specific probe established in the present study could also be useful for the selection of subjects and the monitoring of therapeutic effects in the LAT1‐targeting therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Because LAT1 is a potential therapeutic target as well as a diagnosis biomarker of cancer, the inhibitors of LAT1 have been developed to suppress tumor growth . LAT1 can also be used for tumor‐targeted delivery of anti‐tumor agents such as melphalan and para‐boronophenylalanine in boron neutron capture therapy . Therefore, the LAT1‐specific probe established in the present study could also be useful for the selection of subjects and the monitoring of therapeutic effects in the LAT1‐targeting therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Detta et al demonstrate that LAT1 is involved in the transport of BPA. Wongthai et al reveal that BPA is transported by LAT2 and LAT1, but not LAT3 or LAT4. Although this study did not provide evidence for the involvement of LAT2 and LAT4 in the uptake of 18 F‐FBPA and 14 C‐BPA, inhibition analysis using short interfering RNA would directly elucidate the role that system L isoforms serve in their uptake.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate BPA accumulation and the T/N ratios, PET using 4-borono-2-18 F-fluoro-phenylalanine ( 18 F-FBPA PET) has been performed. [3][4][5][6][7] Previously, we reported that 18 F-FBPA was predominantly transported by L-type amino acid transporter (system L). 8 In rat 9L gliosarcoma cells, 2-aminobicyclo-(2.2.1)-heptane-2-carboxylic acid (BCH) inhibited BPA uptake, which suggested that system L played a role in this phenomenon.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This difficult task could be achieved by the synthesis of a boron compound that is selectively delivered by LAT1. Indeed, p-boronophenylalanine (BPA), a boron compound commonly used in BNCT, is incorporated by LAT1[38-40], suggesting that LAT1 is an optimal mediator for delivery of boron in BNCT. However, since we cannot still completely rule out the possibility of BPA uptake by other transporters, it is necessary to develop compounds that exhibit strict selectivity to LAT1.…”
Section: Clinical Application Of Lat1mentioning
confidence: 99%